Oral Health and Systemic Diseases: Life Sciences-Health - Dr.K.M.K.Masthan, Guest Editor (International Journal of Life Science and Pharma Research, 2021)
Oral and systemic health are closely related to each other. oral diseases are potentially associated with different general health conditions. Thereby, an influence of oral conditions on systemic health or vice versa as well as different bidirectional relationships have been uncovered. Moreover, medications can show distinct side effects in the oral cavity, such as xerostomia or gingival overgrowth, or affect the patient’s immune system as well as bone metabolism. oral diseases can affect the initiation and progress of various systemic diseases such as cardiovascular, neurological, and respiratory diseases; on the other hand, systemic diseases can increase the susceptibility of suffering from oral diseases. Both oral and systemic diseases share several common risk factors, which contribute to the incidence of both diseases, for example, aging, smoking, alcohol abuse, gender, education and socioeconomic status, and genetic susceptibility